Essential oils composition of leaves and flowers of Salvia syriaca L. and S. reuterana Boiss. from Borujerd-Iran - H Lari Yazdi; M Goudarzi; D Yazdani; AK Chehregai (Institue of Medicinal Plants, ACECR, 2005)
Background: The genus Salvia, which belongs to the lamiaceae family, consist of about 700 to 900 spesies widespread throughout the word. In Iran, about 57 species are present, of which some are endemic. Plant belonging to this genus are pharmacologically active and have been used in folk medicine all around the word. Objective: The aim of the present study was to detect and compare the essential oils composition in leaves and flowers of two species of salvia collected from Borujerd. Method: Salvia syriaca and Salvia reuterana was collected in May 2004 from Borujerd, Lorestan province. The essential oil of the leaves and flowers from each plants obtained by hydrodistillation by Clevenger type apparatus was analyzed by GC/MS. Results: The major components in the essential oil of the S. reuterana Leaves were Beta Caryophyllene (13.14 %), Spathulenol (12.39 %), and in S. syrica were Spathulenol (18.63 %), Bornyl Acetate (10.49 %), Alpha cadinene (10.25 %) and Delta Elemen (7.91 %). The major components in the essential oil of the S. reuterana flowers were Beta Caryophyllene (15 %), Isospathulenol (7.73 %), Bornyl Acetate (5.85 %), Beta Elemene (5.98 %), and in S. syriaca were Spathulenol (21.39 %), Bornyl Acetate (9.57 %), Germacrene B (8.37 %), Alpha Pinene (6.12 %), Delta cadinene (5.75 %) and Delta Elemen (5.34 %). Conclusion: This study indicated that the components of the essential oils from the leaves and flowers were different. Some components in flowers were present in higher amounts than in leaves. The major components were Beta Caryophyllene, Spathulenol Germacrene B, Bornyl Acetate and Delta Elemene.